Obsessive passion, opportunity recognition, and entrepreneurial performance: The dual moderating effect of the fear of failure - Tu, Yuqi; Hao, Xiling; Rosak-Szyrocka, Joanna; Vasa, László; Zhao, Xin (Frontiers in Psychology, 2023)
An individual’s strong inclination toward an important or preferred activity is a critical factor that drives them to engage in corresponding activities. This study focuses on how entrepreneurs, influenced by obsessive passion, are motivated to put great effort into taking advantage of business opportunities and accomplishing entrepreneurial goals. The research subjects were founders of startups, and data collection was conducted using a variety of methods. The entire sample data collection process took 6 months, and 208 questionnaires were obtained following a rigorous screening process. Using SPSS and AMOS tools for empirical analysis, this study found that obsessive passion can promote entrepreneurial performance and opportunity recognition plays a mediating role. In addition, we also found that endogenous and exogenous fear of failure play different moderating roles in the effect of obsessive passion on opportunity recognition. The research conclusion not only deepens the theoretical understanding of entrepreneurial passion, opportunity recognition, and fear of failure at a more subtle level but also provides a reference for guiding entrepreneurial practice and education.